Computers! - Trainor, Timothy N. 1953- (Mitchell McGraw-Hill, 1994)
This introduction to computers and computers in society aims to equip students with the knowledge necessary to use computer systems as tools to increase their productivity and effectiveness as users in business and society. Coverage includes hardware, software, business systems and societal issues.